Detection of Neospora caninum and Toxoplasma gondii in Semen of Naturally Infected Rams - de Oliveira Koch, Marilia; Dittrich, Rosangela Locatelli; Weiss, Romildo Romualdo; Bergstein-Galan, Tacia; Aguiar, Daniel Moura; Brandão, Yara de Oliveira; Cruz, Amilcar Arenal; Brenner Busch, Ana Paula; Gomes Monteiro, Ana Lúcia (Acta Scientiae Veterinariae, 2019)
Background: Neospora caninum and Toxoplasma gondii are closely related cyst-forming apicomplexan parasites identified as important causes of reproductive failure in cattle. Moreover, abortion cases attributed to N. caninum and T. gondii infection have been occasionally reported in sheep. Due to the relatively scarce information on the molecular detection of N. caninum in the semen of naturally infected rams, this study aimed to detect parasitic DNA in fresh semen samples and in frozen extended semen straws from male sheep from artificial inseminations centers in Southern Brazil. Materials, Methods & Results: Semen samples of 38 rams from artificial insemination centers were evaluated. Eleven rams were naturally infected (seropositive for anti-N. caninum and/or anti-T. gondii IgG) and were selected for fresh semen collection. We tested all the samples for the closely related protozoan T. gondii to detect a possible cross-reaction and co-infection, due to the close similarity with N. caninum. The indirect fluorescent antibody test was used to detect IgG antibodies in the 11 serum samples from rams. Fresh semen samples were collected from 11 rams on days 1, 50, 55, and 58 using an artificial vagina and ewe in estrus. Other 27 rams had their frozen extended semen straws analyzed. A total of 20 fresh semen samples and 27 frozen extended semen straws samples were used to detect the presence of N. caninum and T. gondii DNA by polymerase chain reaction (PCR). Nc-5 and B1 genes were used as target regions to detect N. caninum and T. gondii DNA, respectively. The presence of N. caninum DNA was confirmed in the third collection of a fresh semen sample of one seropositive ram. T. gondii DNA was detected in a fresh semen sample of one seropositive ram. The DNA sequences of 186 bp from N. caninum (GenBank accession: MH806393) and 492 bp from T. gondii (GenBank accession: MH793503) were obtained by sequencing, and analysis revealed 99% and 100% identity, respectively, compared with other sequences deposited at GenBank. N. caninum and T. gondii DNAs were not detected in any of the 27 frozen extended semen straws used for artificial insemination. Discussion: This study demonstrated the presence of N. caninum and T. gondii DNA in fresh semen samples of naturally infected rams. The non-detection of N. caninum and T. gondii DNA in frozen semen samples of rams could be due to the dilution that was used to prepare the semen straws (GGL diluent and 5% glycerol), since fresh semen samples were not diluted prior to the test. Moreover, in our study, the volume of frozen semen samples (0.25 mL) used for PCR was lower than the volume of sediment obtained from fresh semen (0.5 mL), and the fresh semen centrifugation to obtain the sediment may have grouped the tachyzoites, increasing the sensitivity of the technique employed. No high IgG serological titers were detected in the rams at the time they were eliminating the parasite through fresh semen. The final titer of anti-N. caninum and anti-T. gondii IgGs in serum was 1:100, suggesting chronic infection. It is suggested that a new parasite elimination pathway is occurring among rams used for reproduction, due to the presence of N. caninum and T. gondii DNA in fresh semen samples from seropositive animals. Although the detection of genomic DNA of N. caninum and T. gondii in semen does not necessarily imply the presence of infectious stages of the parasites and does not determine their viability, these results demonstrate the need for further studies. Our study also indicates the need to reinforce preventive measures for sheep in artificial insemination centers until the risks are evaluated, by performing serological examinations with anti-N. caninum and anti-T. gondii antibodies, for instance, to select the rams that will be used for breeding.